Penerapan Konsep Rumah Tumbuh pada Tata Ruang Rumah Swatantra: Studi Kasus Rumah Tempat Tinggal Karya Studio Dasar - ‘Afiah Bima Putriani (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The limited urban land in Greater Jakarta demands the emergence of a residential approach that is more adaptive to the growing needs of space. This study examines the application of the concept of a growing house in the residence of Rumah Swatantra by Studio Dasar. The research method uses a qualitative-descriptive approach through literature studies and direct interviews with the designer architects. The results of the study show that the application of modular patterns and concrete hollow infill structure systems provides the flexibility of space growth without the need to dismantle the basic structure. The process of space growth occurred gradually following the development of the family from 2017 to 2024, and showed that the quality of space can still be maintained even though the building is built in stages. These findings confirm that the concept of growing houses can be an alternative strategy for sustainable housing in urban areas that experience limited land. In addition, this study highlights the importance of careful spatial planning from the early stages of development so that spatial expansion can be carried out efficiently, measurably, and in harmony with the needs of residents. This approach not only improves the comfort and functionality of the space, but also minimizes construction waste and future renovation costs.